Juridical Review of Delik Culpa on Traffic Accident Cases - Hotryan Rivaldo Hamonangan Purba; Ronald Hasudungan Sianturi (Jurnal Syntax Admiration, 2024)
This study aims to determine the application of material criminal law to the crime of traffic negligence that results in the loss of life of another person in decision Number 142/Pid.Sus/2020./PN Jap and to find out the legal considerations by the panel of judges in imposing a penalty in the form of a penalty for the crime of traffic negligence that causes casualties Number 142/Pid.Sus/2020./PN Jap. This research was carried out by collecting data through literature research. In the study, it was found that, in decision number 142/Pid.Sus/2020./PN Jap, the indictment prepared by the Public Prosecutor had met the formal and material requirements. In his demand, the Public Prosecutor demanded that the defendant be guilty of committing the crime of traffic negligence Article 310 paragraphs (4), (3), and (2) No. 22 of 2009 concerning Road Traffic and Transportation by the first indictment, based on the legal facts, both witness statements and the defendant's statements as well as the elements contained in the indictment are considered to have been proven by the Public Prosecutor so that the acts and the elements of the article match each other. The Judge's consideration in Applying criminal provisions against the perpetrators, in this case, is appropriate where the judge has considered both juridical considerations, trial facts, witness statements, existing evidence, judge's beliefs, and support matters. Based on the facts at the trial, the Panel of Judges considered that the defendant could be held responsible for the acts committed with the consideration that the defendant had been legally proven which resulted in the death of another person so the defendant was sentenced to a commensurate sentence.